Sierra Leone : Second Review Under the Extended Credit Facility Arrangement and Financing Assurances Review, and Requests for Augmentation of Access Under the Extended Credit Facility and Debt Relief Under the Catastrophe Containment and Relief Trust. (IMF Staff Country Reports; Country Report ;, 2015)
This paper discusses Sierra Leone's Second Review Under the Extended Credit Facility Arrangement and Financing Assurances Review. Economic output is set to contract by some 13 percent in 2015, comprising a decline in non-iron-ore activity of some 2 percent, and a 47 percent slump in iron-ore output as the dominant mining operator is not expected to resume activity until mid-year at the earliest. Policy discussions focused on generating fiscal space to tackle the Ebola emergency and contend with the effects of the slump in iron-ore production and prices. The IMF staff supports the authorities' request for significant additional financing from the IMF.